Letter from Michael Hamburger to Robin Skelton, [between 1955-1969?] - http://id.worldcat.org/fast/51878 (1955)
Part of a collection of letters from poet and German-English translator Michael Hamburger to Robin Skelton. Most of the correspondence discusses work of Hamburger’s that might be included in publications put together by Skelton.